A perspective on embracing emerging technologies research for organizational behavior - Jestine Philip (Organization Management Journal (OMJ), 2022)
Purpose - Emerging technologies are capable of enhancing organizational- and individual-level outcomes. The organizational behavior (OB) field is beginning to pursue opportunities for researching emerging technologies. This study aims to describe a framework consisting of white, black and grey boxes to demonstrate the tight coupling of phenomena and paradigms in the field and discusses deconstructing OB's white box to encourage data-driven phenomena to coexist in the spatial framework. Design/methodology/approach - A scoping literature review was conducted to offer a preliminary assessment of technology-oriented research currently occurring in OB. Findings - The literature search revealed two findings. First, the number of published papers on emerging technologies in top management journals has been increasing at a steady pace. Second, various theoretical perspectives at the micro- and macro- organizational level have been used so far for conducting technologyoriented research. Originality/value - By conducting a scoping review of emerging technologies research in OB literature, this paper reveals a conceptual black box relating to technology-oriented research. The essay advocates for loosening OB's tightly coupled white box to incorporate emerging technologies both as a phenomenon and as data analytical techniques.
Keywords: 650; Emerging technologies; Artificial intelligence; Machine learning; Organizational behavior; Black box